Therapeutic Properties of Green Tea: A Review - Sonia Ratnani; Sarika Malik (Journal of Multidisciplinary Applied Natural Science, 2022)
The most consumed beverage in the world is tea after water. Till today the consumption of black tea is 70% while that of green tea is only 20%. One reason for this percentage is lack of awareness about green tea and invested research. Green tea along with caffeine which imparts characteristic taste, bitterness and stimulating effect, is also rich in a group of chemicals, called catechin polyphenols (commonly known as tannins, which contribute to bitter taste and astringency) and deliver antioxidant properties. Furthermore, green tea also comprises of amino acids such as Theanine along with alkaloids such as adenine, dimethylxanthine, theobromine, theophylline, and xanthine. Some vitamins, like vitamin A, vitamin B1, vitamin B2, vitamin B3, vitamin C and vitamin E are also found in green tea. The present review gives the study of various constituents of green tea and their impact on human health. Studies provide strong evidence that owing to antioxidant properties daily intake of green tea may be used as a preventive measure for different types of cancer and other diseases. This review gives a detailed analysis of constituents of green tea and highlighting it's potential as a natural nutraceutical. However, although much of the documented literature mentions positive effect yet much had to be explored on correlation between concentration of green tea and toxicity.